Legal protection of life environment in using a coastal fishing resource - Ilyas, .; Abu Thalib, Jasmi bin (Opción, 2019)
This study aimed to analysis the implementation the legal protection of the environmental life into using the fishing resource owned coastal region. The result of this study indicated that the controlling and sanction still not be optimum to secure and safe legal protection for using life environment and its ecosystem in the a coastal resources. All policies have still weakly legal substances and make an overlapping and ambiguity. Hence, the larger implied many more problems and violations in the management of life environment